Collaborative games to develop psychomotor skills and autonomy in children aged 3 to 4 years - Ninasunta Pilaguano, Anabel Vanesa (2024)
The development of psychomotor skills and autonomy in early childhood is crucial because they directly impact the comprehensive growth of the child. Therefore, the objective was aimed at developing psychomotor skills and autonomy in children aged three to four years through collaborative games in the “San José - La Salle” Educational Unit in the province of Cotopaxi-Ecuador. We worked with quantitative methodology, with action research design, descriptive scope and transversal type. The sample was non-probabilistic, consisting of 15 students and 2 Early Education teachers from the aforementioned context. The results showed that the implementation of playful strategies promotes psychomotor development in infants. It was concluded that the proposal proposed in this study positively impacted infants in their psychomotor development and autonomy; Likewise, the importance of continuous training of teachers on these topics was highlighted.